On coupled impulsive fractional integro-differential equations with Riemann-Liouville derivatives - Wang, Xiaoming; Alam, Mehboob; Zada, Akbar (AIMS mathematics, 2021)
In this paper, we investigate the existence, uniqueness and stability of coupled impulsive fractional integro-differential equations with Riemann-Liouville derivatives. To prove the existence and uniqueness results for afore mentioned system, we use the techniques of Kransnoselskiios type fixed point theorem. Furthermore, different kinds of Ulam stabilities are discussed along with examples, to demonstrate the validity of main results.